OVERVIEW OF MINIMUM SERVICE STANDARD CROSSINGTRANSPORT AT KMP. KUALA BATEE II IN ROUTE TANJUNG KALIAN – TANJUNG API –API - Surnata Surnata; Driaskoro Budi Shidarta; Annisa Veranika (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2021)
Tanjung Kalian Port which is managed by PT. ASDP Indonesia Ferry (Persero) Bangka Branch is one of the ports that handles ferry transportation in West Bangka Regency. The route at Tanjung Kalian Harbor is the Tanjung Kalian-Tanjung Api-api route. The purpose of this study was to determine the level of suitability of crossing transportation services above KMP. Kuala Batee II which is in accordance with existing regulations and what aspects must be improved on passenger services, vehicle loading services and ship operating services to comply with the minimum service standards of ferry transportation based on the Regulation of the Minister of Transportation of the Republic of Indonesia. This study uses primary data and secondary data in data acquisition, primary data in the form of observation and documentation methods, while secondary data in the form of institutional and literature. In analyzing the data using the method of analysis of the level of conformity and the Classification of Minimum Service Standards for Ferry Transport. After conducting research and data analysis on the survey results, it can be concluded that KMP. Kuala Batee II has not been able to provide maximum service to service users and Kuala Batee II has not been able to meet ship service speed standards. Therefore it is necessary to improve and add facilities and services so that KMP. Kuala Batee II can meet the minimum service standards for ferry transportation.